THE DYNAMICS OF THE ROMANIAN ENERGY MINING INDUSTRY IN THE EUROPEAN CONTEXT - Corici, Marian Corici Cătălin (Annales Universitatis Apulensis Series Oeconomica, 2017)
The study presents aspects regarding the evolution of the coal industry in Romania in the conditions of alignment with the convergence factors stipulated by the decisionmakers of the community space. In the last century, the Romanian mining industry has witnessed a strong development. The intensification of exploitation activities has intensified considerably as coal demand has been on the rise from one period to the next. Thus, the European directives impose the need to optimize the production costs in the coal industry on the basis of competitiveness in the conditions of obtaining alternative electricity at a lower cost than the one obtained through the combustion of coal.